Analysis Of The Notion Of Decent Work In Its Conceptual, Terminological And Legal Aspects - Vanessa Vieira Pessanha (Revista do Direito do Trabalho e Meio Ambiente do Trabalho, 2016)
The present article deals with the notion of decent work, especially in the conceptual, terminological and legal perspectives, analyzing its scope, its relevance for the realization of the dignity of the human person and how the legal set contemplates and stimulates its practical verification. The objective is to develop a more detailed appreciation of the meaning created by the International Labor Organization, understanding peculiarities and delimiting the application in the legal world. The research is qualitative, with method of bibliographical revision, listing directly related documents (national and international norms) and consulting other sources (official websites and dictionaries).